Comparative Effectiveness of Stereotactic Electroencephalography Versus Subdural Grids in Epilepsy Surgery. Issue 6 (14th October 2021) - Jehi, Lara; Morita‐Sherman, Marcia; Love, Thomas E.; Bartolomei, Fabrice; Bingaman, William; Braun, Kees; Busch, Robyn M.; Duncan, John; Hader, Walter J.; Luan, Guoming; Rolston, John D.; Schuele, Stephan; et al.
Abstract : Objective: The aim was to compare the outcomes of subdural electrode (SDE) implantations versus stereotactic electroencephalography (SEEG), the 2 predominant methods of intracranial electroencephalography (iEEG) performed in difficult‐to‐localize drug‐resistant focal epilepsy. Methods: The Surgical Therapies Commission of the International League Against Epilepsy created an international registry of iEEG patients implanted between 2005 and 2019 with ≥1 year of follow‐up. We used propensity score matching to control exposure selection bias and generate comparable cohorts. Study endpoints were: (1) likelihood of resection after iEEG; (2) seizure freedom at last follow‐up; and (3) complications (composite of postoperative infection, symptomatic intracranial hemorrhage, or permanent neurological deficit). Results: Ten study sites from 7 countries and 3 continents contributed 2, 012 patients, including 1, 468 (73%) eligible for analysis (526 SDE and 942 SEEG), of whom 988 (67%) underwent subsequent resection. Propensity score matching improved covariate balance between exposure groups for all analyses. Propensity‐matched patients who underwent SDE had higher odds of subsequent resective surgery (odds ratio [OR] = 1.4, 95% confidence interval [CI] 1.05, 1.84) and higher odds of complications (OR = 2.24, 95% CI 1.34, 3.74; unadjusted: 9.6% after SDE vs 3.3% after SEEG). Odds of seizure freedom in propensity‐matched resected patients were 1.66 times higher (95% CI 1.21, 2.26) for SEEG compared with SDE (unadjusted: 55% seizure free after SEEG‐guided resections vs 41% after SDE). Interpretation: In comparison to SEEG, SDE evaluations are more likely to lead to brain surgery in patients with drug‐resistant epilepsy but have more surgical complications and lower probability of seizure freedom. This comparative‐effectiveness study provides the highest feasible evidence level to guide decisions on iEEG. ANN NEUROL 2021;90:927–939